Cluster Analysis of Symptoms Among Patients with Upper Extremity Musculoskeletal Disorders - Gold, Judith E. (Springer US, 2010)
Introduction Some musculoskeletal disorders of the upper extremity are not readily classified. The study objective was to determine if there were symptom patterns in self-identified repetitive strain injury (RSI) patients. Methods Members (n = 700) of the Dutch RSI Patients Association filled out a detailed symptom questionnaire. Factor analysis followed by cluster analysis grouped correlated symptoms. Results Eight clusters, based largely on symptom severity and quality were formulated. All but one cluster showed diffuse symptoms; the exception was characterized by bilateral symptoms of stiffness and aching pain in the shoulder/neck. Conclusions Case definitions which localize upper extremity musculoskeletal disorders to a specific anatomical area may be incomplete. Future clustering studies should rely on both signs and symptoms. Data could be collected from health care providers prospectively to determine the possible prognostic value of the identified clusters with respect to natural history, chronicity, and return to work.